2015
DOI: 10.1111/sms.12593
|View full text |Cite
|
Sign up to set email alerts
|

Increased post‐operative cardiopulmonary fitness in gastric bypass patients is explained by weight loss

Abstract: Roux-en-Y gastric bypass (RYGB) leads to a major weight loss in obese patients. However, given that most patients remain obese after the weight loss, regular exercise should be part of a healthier lifestyle. The primary aim of this study was to investigate the cardiopulmonary fitness in obese patients before and after RYGB. Thirty-four patients had body composition and cardiopulmonary fitness (VO ) assessed and completed questionnaires regarding physical activity and function twice before RYGB (time points A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…It is known that insulin sensitivity, GLUT4 protein and mitochondrial content are highest in type I (red, oxidative) fibres, compared with type II (white, glycolytic) fibres and that insulin sensitivity increases with training status . Therefore, a change in fibre type composition or exercise habits could have influenced the data, but no change in fibre type composition (Figure ), GLUT 4 content or cardiorespiratory fitness per body weight was seen in this cohort.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is known that insulin sensitivity, GLUT4 protein and mitochondrial content are highest in type I (red, oxidative) fibres, compared with type II (white, glycolytic) fibres and that insulin sensitivity increases with training status . Therefore, a change in fibre type composition or exercise habits could have influenced the data, but no change in fibre type composition (Figure ), GLUT 4 content or cardiorespiratory fitness per body weight was seen in this cohort.…”
Section: Discussionmentioning
confidence: 72%
“…The present study is part of a larger project investigating the metabolic and psychosocial effects of gastric bypass surgery. Design and methods of this study have been reported previously . The complete protocol was approved by the Copenhagen ethics committee (journal no.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project investigating the metabolic and psychosocial effects of RYGB up to 18 months postoperatively . In the longitudinal part of the study, 18 patients with morbid obesity and a wide range of IS were included.…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47] A full set of muscle biopsies from fifteen subjects with obesity (7 with (OB-DM2) and 8 without (OB) T2D) scheduled for laparoscopic RYGB were available at 4 time points: (i) at inclusion, (ii) after a voluntary diet-induced 8% body weight loss, (iii) 4 months and (iv) 1.5 years after RYGB surgery. [41][42][43][44][45][46][47] A full set of muscle biopsies from fifteen subjects with obesity (7 with (OB-DM2) and 8 without (OB) T2D) scheduled for laparoscopic RYGB were available at 4 time points: (i) at inclusion, (ii) after a voluntary diet-induced 8% body weight loss, (iii) 4 months and (iv) 1.5 years after RYGB surgery.…”
Section: Subjects and Interventionmentioning
confidence: 99%
“…The present project is part of a larger project (GASMITO) investigating the metabolic and psycho-social effects of RYGB surgery. [41][42][43][44][45][46][47] A full set of muscle biopsies from fifteen subjects with obesity (7 with (OB-DM2) and 8 without (OB) T2D) scheduled for laparoscopic RYGB were available at 4 time points: (i) at inclusion, (ii) after a voluntary diet-induced 8% body weight loss, (iii) 4 months and (iv) 1.5 years after RYGB surgery. Muscle biopsies from five lean and sedentary male subjects, recruited as previously reported 48 under the MITOBOLISM project, were analysed as reference group (RG).…”
Section: Subjects and Interventionmentioning
confidence: 99%